Modeling spatial knowledge for generating verbal and visual route directions - Schuldes, Stephanie; Roth, Michael; Krömker, Susanne; Frank, Anette (Knowledge-Based and Intelligent Information and Engineering Systems, 2011)
Challenges in the development of state-of-the-art navigation tools involve the synchronous generation of user-tailored natural language directions and accompanying graphical representations. Of particular interest is the combination of indoor and outdoor scenarios. We describe an architecture for simultaneously generating route directions and suitable visualizations of the navigational context for walking directions.